The Unease Modulation Model: An Experiential Model of Stress With Implications for Health, Stress Management, and Public Policy - Arpaia, Joseph; Andersen, Judith P. (Frontiers in Psychiatry, 2019)
Stress has a pervasive, global and negative influence on individual health. Stress also has negative effects on families, organizations, and communities. Current models of stress are either too general or too detailed to guide effective interventions across the spectrum of medical and social conditions that are stress-related. A new model is needed that explains how stress can have such varied effects and describes how to reduce its harm. The model also must capture both the dynamic nature of stress and its ability to persist and cause chronic effects. The model must guide those who use it in selecting effective interventions and in developing more effective interventions. Ideally the model will be helpful to people who are experiencing stress and do not have access to professional help. The authors propose a model in an attempt to address the above concerns. The proposed model is called the Unease Modulation Model (UM-Model). Briefly, the UM-Model separates stress into several elements common to people’s experience. The model describes how these elements interact and how those interactions lead to recurring states that are associated with health or illness. Finally, the model enables the person under stress to identify the elements where they will have the most leverage to evoke change and apply specific, effective techniques for that purpose. While the model is experiential it is also based on mathematical theories of perception, non-linear dynamics, neurophysiology, and cognitive psychology. In spite of this underlying sophistication it can be used by those without a medical education. The proposed model has been taught successfully to patients in a clinical setting. The model is now being used in an international training program with police officers to address the long-term stress associated with the career, and reduce decision-making errors regarding use-of-force. This article introduces the model by defining components based on patient descriptions of stress and integrating those into a formal structure. We then demonstrate how the model can be applied to a number of medical and psychiatric conditions. The article concludes by briefly discussing the model's application to family and societal stress-related difficulties.